CONVERSATION ANALYSIS IN A MOVIE ‘LIFE OF PI’ - Zahrra Oktavia Savitri G. (Airlangga Development Journal, 2022)
This study is called “Conversation Analysis in a movie ‘Life of Pi’”. Data source of this study is taken from the movie script of ‘Life of Pi’ that rewrite by David Mage based on the same title novel by the writer Yann Martel. This is the selected movie because it is the incredible and success movie that give rise to critics and compliment from many sides. This film succeeds into some movie international award and at the same time won in a few categories. The scope of discussion is limited by both theory that is “Context of Situation” theory by Halliday and Hasan and “Gricean Maxim” theory by Grice. The next selected data will be analyzed with qualitative method. Some points of both related theories are Field, Tenor, Mode, Quantity Maxim, Quality Maxim, Relation Maxim, and Manner Maxim. Analysis of every point manage to express the meaning from the selected conversation before. The invention of this study is meaning starring by the utterances from conversations of the related movie.